Identification of Inhibitors of the Association of ZAP-70 with the T Cell Receptor by High-Throughput Screen. (March 2017) - Visperas, Patrick R.; Wilson, Christopher G.; Winger, Jonathan A.; Yan, Qingrong; Lin, Kevin; Arkin, Michelle R.; Weiss, Arthur; Kuriyan, John
ZAP-70 is a critical molecule in the transduction of T cell antigen receptor signaling and the activation of T cells. Upon activation of the T cell antigen receptor, ZAP-70 is recruited to the intracellular ζ-chains of the T cell receptor, where ZAP-70 is activated and colocalized with its substrates. Inhibitors of ZAP-70 could potentially function as treatments for autoimmune diseases or organ transplantation. In this work, we present the design, optimization, and implementation of a screen for inhibitors that would disrupt the interaction between ZAP-70 and the T cell antigen receptor. The screen is based on a fluorescence polarization assay for peptide binding to ZAP-70.